Interleukin 21 Receptor Affects Adipogenesis of Human Adipose-Derived Stem/Stromal Cells. (10th January 2022) - Falavinha, Bruna Cristina; Barisón, María Julia; Rebelatto, Carmen Lúcia Kuniyoshi; Marcon, Bruna Hilzendeger; de Melo Aguiar, Alessandra; da Silva, Evelin Brandão; Stimamiglio, Marco Augusto; Shigunov, Patrícia
Abstract : Dysfunctions in adipose tissue cells are responsible for several obesity-related metabolic diseases. Understanding the process of adipocyte formation is thus fundamental for understanding these diseases. The adipocyte differentiation of adipose-derived stem/stromal cells (ADSCs) showed a reduction in the mRNA level of the interleukin 21 receptor (IL21R) during this process. Although the receptor has been associated with metabolic diseases, few studies have examined its function in stem cells. In this study, we used confocal immunofluorescence assays to determine that IL21R colocalizes with mitochondrial protein ATP5B, ALDH4A1, and the nucleus of human ADSCs. We demonstrated that silencing and overexpression of IL21R did not affect the cell proliferation and mitochondrial activity of ADSCs. However, IL21R silencing did reduce ADSC adipogenic capacity. Further studies are needed to understand the mechanism involved between IL21R and the adipogenic differentiation process.